Sex knowledge and attitudes of high school students in a selected Catholic school, 1975-1976 - Baltazar, Ruby Ramos 1949-
The aim of the study was to determine the sex knowledge and attitudes of high school students in a selected Catholic school during the school year 1975-1976 for the purpose of deriving the implications of the findings for sex education. The normative survey was utilized to determine the sex knowledge and attitudes of 349 high school students. The results showed that high school students had no knowledge on the majority of the sex terms. The attitudes of high school students toward sex were slightly unfavorable. Majority of students obtained scores below the mean score